Prevalence of cleft lip and palate in Bauru, SP – concordance among registries of HRAC/USP, DNV and SINASC - Molena, Kelly Fernanda; Winckler, Vivian Patricia Saldias Vargas; Dalben, Gisele da Silva (Brazilian Dental Science, 2021)
Objective: Congenital defects, including cleft lip and palate, increase the morbidity and mortality in the affected population. This study aimed to determine the prevalence of cleft lip and palate in the city of Bauru, Brazil, by evaluation of registry in the Brazilian Livebirth Certificate (DNV) and the Information System on Livebirths (SINASC), and analyzed the concordance of diagnosis compared with registries of the Hospital for Rehabilitation of Craniofacial Anomalies (HRAC/USP), located in the same city. Material and Methods: This retrospective observational study comprised analysis of all DNVs and identification of individuals with clefts born and living in Bauru, comparing with data from HRAC/USP. The prevalence was calculated by dividing the number of children born with clefts in the study period by the total number of livebirths registered. The reporting of different types of clefts was compared by the chi-square test. Results: Overall, 50,898 DNV were evaluated, among which there were 25 reported cases of cleft lip and/or palate. In the same period, HRAC/USP registered 77 cases born in Bauru, representing 67.5% of underreporting of the occurrence of clefts. Cleft palate was the most prevalent (34.9%), followed by cleft lip and palate (31.7%) and cleft lip (30.2%), mostly affecting males (58.5%). The reporting of cleft palate (16.12%) was lower compared to cleft lip (43.75%) and cleft lip and palate (54.54%). Conclusion: The study revealed predominance of cleft palate, with significant underreporting of clefts in the public health system, especially for cleft palate as compared to cleft lip and cleft lip and palate. Keywords Cleft lip; Cleft palate; Epidemiology; Prevalence; Reporting.